2021
DOI: 10.1111/pan.14179
|View full text |Cite
|
Sign up to set email alerts
|

The virtual pediatric perioperative home, experience at a major metropolitan safety net hospital

Abstract: Introduction: Successes from anesthesiologist-led perioperative surgical homes in the adult patient population have inspired similar initiatives by pediatric hospitals. Typically the care coordination for these perioperative homes is run through hospital-funded, on-site, preanesthesia clinics. Preliminary data from pediatric perioperative homes have shown promising results in improved patient outcomes and decreased length of hospital stay. The majority of pediatric surgeries within the country are performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The most common CCSRs, which cumulatively accounted for just over half of the increase in the MS-DRG weighting factor, in descending order of the point estimates, were spine fusion, heart valve surgery, colectomy, pulmonary resection, coronary artery bypass graft, and hip and knee arthroplasty (Table 3). These CCSRs include the surgical procedures commonly targeted for interventions to reduce complications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], confirming the face validity of our method of using the MS-DRG weighting factor to measure incremental societal costs of complications. The impact of each additional case with an escalation in the MS-DRG differed greatly among the CCSRs.…”
Section: Percentile Shares For Ccsrs and The Causative Diagnoses Amon...mentioning
confidence: 52%
See 2 more Smart Citations
“…The most common CCSRs, which cumulatively accounted for just over half of the increase in the MS-DRG weighting factor, in descending order of the point estimates, were spine fusion, heart valve surgery, colectomy, pulmonary resection, coronary artery bypass graft, and hip and knee arthroplasty (Table 3). These CCSRs include the surgical procedures commonly targeted for interventions to reduce complications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], confirming the face validity of our method of using the MS-DRG weighting factor to measure incremental societal costs of complications. The impact of each additional case with an escalation in the MS-DRG differed greatly among the CCSRs.…”
Section: Percentile Shares For Ccsrs and The Causative Diagnoses Amon...mentioning
confidence: 52%
“…Efforts to validate the cost-effectiveness of such expansion of anaesthesiologists' role outside the operating room proper have generally been conducted at single institutions, with most patients cared for by small numbers of surgeons [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This observation should not be construed as a criticism but rather reflects the complexity of PSH implementation within organizations and the relatively small numbers of surgeons within each surgical subspecialty at most individual hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 One recent study demonstrated a significant reduction in same-day surgery cancellations in children undergoing care at a safetynet institution in New England after introduction of a virtual PSH, suggesting that virtual evaluation was effective in identifying patients that were not medically optimized for surgery. 61 Virtual visits can similarly be used to address social and cultural impediments to care.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most disruptive events is an unexpected case cancellation, with a reported rate of between 0.34% to 44.2%, but diverse methodologies hamper comparisons between studies [2,. In most cases, cancellations occur within 24 h of surgery, but they also occur after induction of anesthesia [29]. Rescheduling cases may not necessarily lead to in-creased workload variability, but it does affect patient satisfaction and enterprise bottom line [30].…”
Section: Introductionmentioning
confidence: 99%